Multiomic analysis identifies a high-risk signature that predicts early clinical failure in DLBCL - Kerstin Wenzl; Matthew E. Stokes; Joseph P. Novak; Allison M. Bock; Sana Khan; Melissa A. Hopper; Jordan E. Krull; Abigail R. Dropik; Janek S. Walker; Vivekananda Sarangi; Raphael Mwangi; Maria Ortiz; et al. (Blood Cancer Journal, 2024)
Abstract Recent genetic and molecular classification of DLBCL has advanced our knowledge of disease biology, yet were not designed to predict early events and guide anticipatory selection of novel therapies. To address this unmet need, we used an integrative multiomic approach to identify a signature at diagnosis that will identify DLBCL at high risk of early clinical failure. Tumor biopsies from 444 newly diagnosed DLBCL were analyzed by WES and RNAseq. A combination of weighted gene correlation network analysis and differential gene expression analysis was used to identify a signature associated with high risk of early clinical failure independent of IPI and COO. Further analysis revealed the signature was associated with metabolic reprogramming and identified cases with a depleted immune microenvironment. Finally, WES data was integrated into the signature and we found that inclusion of ARID1A mutations resulted in identification of 45% of cases with an early clinical failure which was validated in external DLBCL cohorts. This novel and integrative approach is the first to identify a signature at diagnosis, in a real-world cohort of DLBCL, that identifies patients at high risk for early clinical failure and may have significant implications for design of therapeutic options.